ANALISIS SWOT DAYA SAING SEKOLAH: STUDI KASUS DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 PASIR PENYU INDRAGIRI HULU, RIAU - Rini Setyaningsih; Herlin Wulandari (Universitas Pakuan, 2020)
SCHOOL COMPETITIVENESS SWOT ANALYSIS: A CASE STUDY IN SMKN 1 PASIR PENYU INDRAGIRI HULU, RIAUOne of the characteristics to see the competitiveness of a school is its accreditation ranking. Schools that have been accredited A can be said to have a great opportunity in developing effective strategies to improve competitiveness. The purpose of this study was to determine the strategic position of SMK N 1 Pasir Penyu with SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). All data were found by researchers through interviews, literature studies, observations, and documents, and questionnaires. Analysis of the data the researcher did was IFAS and EFAS, then SWOT analysis to find out some internal and external factors and to identify a strategic position of SMK N 1 Pasir Penyu. The results of this study indicate that SMK N 1 Pasir Penyu is located in quadrant I position (Aggressive), which means that SMK N 1 Pasir Penyu is in the survival stage. Researcher's suggestion for SMK N 1 Pasir Penyu is to be able to fix several internal weaknesses. To be able to avoid and reduce the threat of competition between schools, SMK 1 Pasir Penyu can create a unique competition as a differentiator between similar schools.